2019
DOI: 10.1002/jbt.22425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined administration of calcium, iron, zinc, chrysanthemum flavonoids, and DMSA on the treatment of lead intoxication in mice

Abstract: The effect of combined administration of calcium (Ca), iron (Fe), zinc (Zn), chrysanthemum flavonoids, and meso-2,3-dimercaptosuccinic acid (DMSA) on the treatment of lead (Pb) intoxication in mice was studied. One hundred ninety female mice (SPF level, aged 18-22 days) were randomly divided into two groups as experimental animals. Mice in group I (10 mice) served as normal control animals, and were administered deionized water containing 12.5 μL/L acetate acid for 6 weeks, whereas mice in group II (180 mice) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Some antagonistic drugs can also reduce the damage of lead to the body by enhancing the body's immunity or antioxidant capacity, such as beetroot juice and laver ( 9 , 10 ). Ions such as calcium, iron, zinc, and magnesium have been also reported to have the ability to reduce the absorption of lead by competing with lead for intestinal absorption ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some antagonistic drugs can also reduce the damage of lead to the body by enhancing the body's immunity or antioxidant capacity, such as beetroot juice and laver ( 9 , 10 ). Ions such as calcium, iron, zinc, and magnesium have been also reported to have the ability to reduce the absorption of lead by competing with lead for intestinal absorption ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…was used as Hangbaiju in China and is rich in volatile oils, flavonoids, phenolic acids, and polysaccharides. Recently, pharmacological studies have revealed that it has broad bioactivities, such as anti-inflammatory, antitumor, relieving diabetes, and antioxidative damage activities [ 6 , 7 ]. It has been proved that chrysanthemum extract can improve the specific skin inflammation in mice and has the potential to treat various immune-related skin diseases [ 8 ].…”
Section: Introductionmentioning
confidence: 99%